2020
DOI: 10.7717/peerj.10068
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of quorum sensing LuxR-type transcriptional regulator, EasR in Enterobacter asburiae strain L1

Abstract: Over the past decades, Enterobacter spp. have been identified as challenging and important pathogens. The emergence of multidrug-resistant Enterobacteria especially those that produce Klebsiella pneumoniae carbapenemase has been a very worrying health crisis. Although efforts have been made to unravel the complex mechanisms that contribute to the pathogenicity of different Enterobacter spp., there is very little information associated with AHL-type QS mechanism in Enterobacter spp. Signaling via N-acyl homoser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Samples that are undetected for the target and for the internal control are invalidated, preventing false-negative results. Some SARS-CoV-2 RT-LAMP studies use an internal control from RT-qPCR (Lau et al 2020 ; Osterdahl et al 2020 ; Zhang and Tanner 2020 ) however, the objective is not performing any sophisticated additional technique and validation for the point-of-care application. With that in mind, the present study showed for the first time the essential role of the internal control in RT-LAMP context, evaluating the performance of the primers and the clinical relevance of the method.…”
Section: Discussionmentioning
confidence: 99%
“…Samples that are undetected for the target and for the internal control are invalidated, preventing false-negative results. Some SARS-CoV-2 RT-LAMP studies use an internal control from RT-qPCR (Lau et al 2020 ; Osterdahl et al 2020 ; Zhang and Tanner 2020 ) however, the objective is not performing any sophisticated additional technique and validation for the point-of-care application. With that in mind, the present study showed for the first time the essential role of the internal control in RT-LAMP context, evaluating the performance of the primers and the clinical relevance of the method.…”
Section: Discussionmentioning
confidence: 99%
“…These are generated by a LuxR homolog, which has been found to decrease bacterial adhesion and downregulate biofilm development [ 57 ]. In E. asburiae , the QS pathway is triggered by C4-HSL and C6-HSL, which bind to their cognate EasR receptor protein (the transcriptional regulator lux R homolog), thus triggering QS-associated gene transcription, as well as its related phenotypes and biofilm formation [ 58 ].…”
Section: Qs-mediated Drug Resistance and Bacterial Virulence In Eskap...mentioning
confidence: 99%
“…Domain analysis (Pfam) revealed two principal conserved domains in VfqR: N-terminal AHL-binding domain (residues 16–163) and C-terminal DNA binding HTH domain (residues 174–230). Sequence alignments of VfqR with canonical LuxR homologs revealed the presence of strongly conserved residues both in the AHL-binding domain (W61, Y65, D74, P75, W89, G114) and the DNA-binding domain (E180, W186, G190) which are present in at least 95% of LuxR-type proteins [ 35 , 36 ] ( Fig. 2 A).…”
Section: Resultsmentioning
confidence: 99%